Default In The Agreement For The Results Of Rice - Mohamad Saprudin Hasim (Estudiante Law Journal, 2019)
Abstract: This paper aims to find out and analyze how the default in the production sharing agreement for cultivating rice fields is viewed from the law. No. 2 of 1960 concerning Agricultural Production Sharing Agreements and the factors that influence the occurrence of default in the production sharing agreement for cultivating rice fields in terms of the Act. No. 2 of 1960 concerning Agricultural Production Sharing Agreements in Gorontalo Regency. This type of research is empirical research.The results of the study show that the default in the profit sharing agreement for cultivating rice fields is viewed from the Law. No. 2 of 1960 concerning Agricultural Production Sharing Agreements in Gorontalo Regency are still being finalized by means of customary deliberations involving the village head as a facilitator. Although there are official regulations by the government, namely UU. No. 2 of 1960 concerning Agricultural Production Sharing Agreements which have clearer arrangements, but until now the provisions of the law have not been applied as expected, it can even be said not to apply at all, it's all because of the regulations of the Act. No. 2 of 1960 concerning the Agricultural Production Sharing Agreement concerning the production sharing agreement was felt by the community to be too complicated. Whereas the factors that influence the occurrence of default in the profit sharing agreement for cultivating rice fields are reviewed from the Law. No. 2 of 1960 concerning Agricultural Production Sharing Agreements in Gorontalo Regency is influenced by internal and external factors. Keywords: Wanprestasi, Agreement, Profit Sharing